2012
DOI: 10.3174/ajnr.a3202
|View full text |Cite
|
Sign up to set email alerts
|

Microcatheter to Recanalization (Procedure Time) Predicts Outcomes in Endovascular Treatment in Patients with Acute Ischemic Stroke: When Do We Stop?

Abstract: BACKGROUND AND PURPOSE: Endovascular treatment for acute ischemic stroke consists of various mechanical and pharmacologic modalities used for recanalization of arterial occlusions. We performed this study to determine the relationship among procedure time, recanalization, and clinical outcomes in patients with acute ischemic stroke undergoing endovascular treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 24 publications
3
30
0
1
Order By: Relevance
“…In the poor collateral group, PRT of Ͼ60 minutes was strongly associated with decreased odds of favorable outcome, which can be a practical marker for the determination of endovascular therapy termination. A previous study showed that the procedural time in intra-arterial treatment is a critical determinant of outcomes, 28 and further negative impact on favorable outcome was shown in the poor collateral group in our study.…”
Section: Discussionsupporting
confidence: 46%
“…In the poor collateral group, PRT of Ͼ60 minutes was strongly associated with decreased odds of favorable outcome, which can be a practical marker for the determination of endovascular therapy termination. A previous study showed that the procedural time in intra-arterial treatment is a critical determinant of outcomes, 28 and further negative impact on favorable outcome was shown in the poor collateral group in our study.…”
Section: Discussionsupporting
confidence: 46%
“…A recent study highlighted the possibility of using procedure time as an appropriate metric for predicting patient outcomes, with target goals of <60 minutes. 20 Although the time to successful reperfusion may hold more physiological relevance than puncture time in determining treatment efficacy, difficulty remains in quantifying this end point because of the presence of partial recanalization that occurs before complete revascularization. 21 Despite advances in device technology to enhance reperfusion rates and reduce procedure times, outcomes have not yet improved, 6,22 which may reflect our current systems of care in transferring patients.…”
Section: Discussionmentioning
confidence: 99%
“…A sensitivity analysis was performed after exclusion of the study with only discharge outcomes. 11 Finally, we repeated the pooled analysis with the use of a 2-stage meta-analysis approach in which individual logistic regression models were fit for each study and summarized by use of random-effects meta-analysis. 17 Because of the small sample sizes in the individual studies, we included only age and pretreatment NIHSS score in the multivariable analysis.…”
Section: Discussionmentioning
confidence: 99%
“…All studies were approved by local institutional review boards. Observational data sources included 1 center in France (University Bichat Hospital, Paris), 9 1 center in Spain (Vall D' Hebron Hospital, Barcelona), 10 a multicenter data set in the United States (University of Minnesota, Hennepin County Medical Centers, University of Medicine and Dentistry of New Jersey), 11 1 center in the Czech Republic (University Ostrava Hospital), 12 and 1 center in the United States (University of Buffalo, New York). 13 A pooled analysis of the 2 IMS trials 3 and a single-center experience study 2 have previously reported the impact of ORT on good clinical outcome, but none has studied associations with 90-day mortality.…”
Section: Data Sourcesmentioning
confidence: 99%
See 1 more Smart Citation